Valuasi Ekonomi Kawasan Museum Adityawarman Kota Padang dengan Metode Biaya Perjalanan (Travel Cost Method) - Putri, Monica; Irfan, Muhammad (Universitas Negeri Padang, 2023)
This study aims to estimate the economic value of cultural tourism at the Adityawarman Museum and analyze the factors that influence the number of visits to the Adityawarman Museum. The economic assessment of the Adityawarman Museum uses primary data from a survey of 205 visitors using the Travel Cost Method (TCM) approach to estimate willingness to pay (WTP) and economic valuation. Using the Ordinary Least Square (OLS) and Poisson Regression (PR) regression methods, the results of this study indicate that the economic value of cultural tourism at the Adityawarman Museum has a potential value of Rp. 143,591,814.80 (on OLS) and Rp. 248,757,673.29 (in PR) if the visitor's WTP is Rp. 8,162.80 (on OLS) and Rp. 14141.19 (on PR). The WTP value obtained is above the price of the entrance ticket. Factors that affect tourist visits are travel costs, age of visitors, level of education of visitors, the existence of other tourist destinations that one wants to visit and the main attraction of the museum. The recommendations given should be for the improvement or development of the museum, a policy of increasing the price of admission tickets can be implemented.